Carbon footprint of a traditional Chinese distilled spirit (Baijiu) with high-resolution supply-chain mapping - Hao Lu; Yisen Qian; Lyujun Chen; Wei Zhou; Kun Yan; Tianshu Ji; Yongtao Tang; Jinping Tian (Resources, Conservation and Recycling, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Comparison of the polluted dust plume and natural dust air mass in a spring dust event in Beijing 2023 - Zhenyi Chen; Zhonghao Zhou; Chengli Ji; Zhiliang Yao; Jiajia Mao; Zhicheng Wang; Yan Xiang; Tianshu Zhang; Yi Zhou; Zijian Chen; Gang Dou (Journal of Environmental Sciences, 2025)

Coupling use of stable isotopes and functional genes as indicators for the impacts of artificial restoration on the carbon storage of a coastal wetland invaded by Spartina alterniflora, southeastern China - Tianshu Chu; Danyang Li; Yi-Jia Shih; Yuqing Guo; Kai Liu; Fenfen Ji; Jun Li; Yuzhu Yin; Ruohai Chen (Frontiers in Marine Science, 2024)
Coastal wetlands are characterized by high production and thus play an important role in global climate change. In past decades, the invasion of Spartina alterniflora has caused many problems of coastal wetlands in southeastern China, and the restoration of such areas was mainly conducted by replacing Spartina alterniflora with mangrove plants. This may impact the carbon storage dynamics in such areas. In this study, stable isotopes (δ 13 C and δ 15 N) and molecular analysis were used to reveal the impact of artificial restoration on the carbon storage of Quanzhou Bay Estuary Wetland Natural Reserve. The major results are as follows: (1) the change in dominant plants results in a changing major source of soil organic matter, from external sources to mangrove plants; (2) the decrease in soil organic matter following the removal of Spartina alterniflora may be primarily caused by the loss of external organic matter, while the production of mangroves may offset such loss and enhance the content and stability of carbon storage over the long term; (3) microbial CO 2 assimilation may serve as an alternative source of bioavailable carbon and thus support the activity of benthic community. Our results revealed the long-term benefits of such restoration on the carbon storage function of wetlands invaded by Spartina alterniflora . Furthermore, the integrating of isotopic tracers and molecular technology may provide new insights in understanding the response of the carbon storage in coastal areas to human activity.

Comparison of the ozone formation mechanisms and VOCs apportionment in different ozone pollution episodes in urban Beijing in 2019 and 2020: Insights for ozone pollution control strategies - Yunfeng Li; Zhenhai Wu; Yuanyuan Ji; Tianshu Chen; Hong Li; Rui Gao; Likun Xue; Yafei Wang; Yuxi Zhao; Xin Yang (Science of The Total Environment, 2024)